Influence of Retinal Degeneration Stages on RGC Threshold under epiretinal electrical stimulation: A Modeling Study. Issue 1 (March 2021) - Zheng, Shiwei; Zhou, Wenqi; Song, Xiaoyu; Li, Liming
Abstract: Retinal prosthesis is an effective treatment to restore partial functional vision for degeneration diseases such as retinitis pigmentosa (RP). The persistent degeneration of the retina can influence the effect of retina prosthesis. However, how the different stages of retinal degeneration influence the retinal ganglion cell (RGC) responses to external electric stimulation remains unclear. In our present study, we established the multilayer retinal model of normal mouse and retinal degeneration (rd1) mouse in different degeneration stages (early, middle and late stage). Meanwhile, the morphology-realistic RGC models with membrane dynamics in different degeneration stages were also established. The effects of retinal structure, ganglion cell morphology and Na + conductance on RGC threshold in response to electrical stimulation were explored. The simulation results showed that the RGC threshold of early degeneration stage was basically the same as that of the normal retina. While the thresholds of middle and late degeneration stages were both higher than that of the early stage, and the late stage showed a higher RGC threshold than the middle stage. This study would provide theoretical support for personalizing design of visual prostheses to treat different degeneration stages of RP patients.